Major considerations of orthognathic surgery in treating obstructive sleep apnea syndrome: a systematic review - Martineli, Marcely Fonn (2024)
Introduction: In the setting of airway obstruction, obstructive sleep apnea syndrome (OSAS) is associated with several comorbidities. Patient evaluation includes a detailed history, clinical and radiographic examination, endoscopy, and polysomnography. Treatment may be nonsurgical or surgical, and Phase II of the Stanford Protocol for surgical treatment involves maxillomandibular advancement. Objective: It was conducted a systematic review to present the main considerations of orthognathic surgery in treating obstructive sleep apnea syndrome. Methods: The systematic review rules of the PRISMA Platform were followed. The search was carried out from June to August 2024 in the Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: A total of 92 articles were found. A total of 22 articles were fully evaluated and 17 were included and developed in the present systematic review study. Considering the Cochrane tool for risk of bias, the overall assessment resulted in 48 studies with a high risk of bias and 22 studies that did not meet GRADE and AMSTAR-2. Most studies showed homogeneity in their results, with X2=82.4%>50%. It has been concluded that orthodontists should perform appropriate screening for obstructive sleep apnea. This can be done as part of our health history, our clinical examination, and review of radiographs taken for purposes other than diagnosis and screening for OSA. Orthodontic treatment for obstructive sleep apnea syndrome can be helpful and effective. However, this can only be done after referral to the appropriate medical specialist, as part of a multidisciplinary team, with consideration of the likely efficacy of the treatment, and after all likely and potential negative consequences have been considered and discussed thoroughly with the patient. Orthognathic surgery combined with soft tissue surgery is most effective as a curative treatment for obstructive sleep apnea syndrome.